4H-SiC superjunction trench MOSFET with reduced saturation current. (January 2019) - He, Qingyuan; Luo, Xiaorong; Liao, Tian; Wei, Jie; Deng, Gaoqiang; Sun, Tao; Fang, Jian; Yang, Fei
Abstract: A novel 4H-SiC superjunction trench metal oxide semiconductor field effect transistor (SJ-TMOS) is proposed in this paper. The device features a grounded P+ buried layer below the P-body, an oxide trench beneath the gate, and a P-region surrounding the oxide trench. The P-region, grounded P+ buried layer, and P-body serve as a three-level buffer (TLB) to lower the saturation current and thus improve the short-circuit ruggedness. Moreover, the P-region, P+ buried layer and N-drift form an SJ structure to decrease the specific on-resistance ( R on, sp ) and increase the breakdown capability. Compared with conventional trench MOSFET (C-TMOS), the saturation current for SJ-TMOS is drastically lowered and thus the short-circuit time ( t sc ) extends by 175%. Meanwhile, the R on, sp decreases by 45% and the breakdown voltage increases by 10%. In addition, the SJ-TMOS exhibits a low gate-to-drain charge ( Q gd ) due to the low permittivity of oxide trench and the nonlinearity in SJ capacitance characteristics. Highlights: The three-level buffer of the proposed device lowers the saturation current and thus improves the short-circuit ruggedness. The superjunction structure reduces the specific on-resistance and improves the breakdown voltage. The P-region and the grounded P+ buried layer shield the trench and thus reduce the electric field in oxide. The low switching loss is caused by the low gate-to-drain charge.